2021
DOI: 10.1038/s41562-021-01139-z
|View full text |Cite
|
Sign up to set email alerts
|

A global analysis of the impact of COVID-19 stay-at-home restrictions on crime

Abstract: The stay-at-home restrictions to control the spread of COVID-19 led to unparalleled sudden change in daily life, but it is unclear how they affected urban crime globally. We collected data on daily counts of crime in 27 cities across 23 countries in the Americas, Europe, the Middle East and Asia. We conducted interrupted time series analyses to assess the impact of stay-at-home restrictions on different types of crime in each city. Our findings show that the stay-at-home policies were associated with a conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
169
0
10

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(190 citation statements)
references
References 47 publications
11
169
0
10
Order By: Relevance
“…The COVID-19 pandemic and first lockdown orders led to rapid changes in everyday routine activities, which had direct effects on opportunities for crime (Nivette et al, 2021). Immediately after the first stay-at-home orders came into force in many countries in March 2020, many researchers noted that various forms of property and violent crime had suffered a notable decrease due to the reduced opportunities for offenders to converge with targets in physical settings (Abrams, 2021;Ashby, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The COVID-19 pandemic and first lockdown orders led to rapid changes in everyday routine activities, which had direct effects on opportunities for crime (Nivette et al, 2021). Immediately after the first stay-at-home orders came into force in many countries in March 2020, many researchers noted that various forms of property and violent crime had suffered a notable decrease due to the reduced opportunities for offenders to converge with targets in physical settings (Abrams, 2021;Ashby, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in recorded crime were also found in Sweden (Gerell et al, 2020), Mexico (Estévez-Soto, 2021), China (Borrion et al, 2020) and Australia (Payne et al, 2021). Nivette et al (2021) recorded crime data from 27 cities across 23 countries and concluded that stayat-home orders contributed to a considerable global drop in urban crime. Some researchers noted, however, that while many types of offline crime were decreasing, there were signs that the changes in routine activities brought about by the first lockdown had increased opportunities for online crime.…”
Section: Rapid Social Changes and Crime: The Covid-19 Casementioning
confidence: 95%
See 2 more Smart Citations
“…In another study by Fana et al, 2020, they reported the Sevier effect of lockdown on employment in Spain, Italy, and the UK [46]. Another study by Nivette et al, 2021, reported a significant increase in crime among urban people in 23 countries of the Americas, Europe, the Middle East, and Asia [47]. Such long-time social erosion will also affect the total social bonding and systems.…”
Section: Possible Social Complications Of Outbreaks In the Near Futurementioning
confidence: 98%